The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1002/ejoc.200300769
|View full text |Cite
|
Sign up to set email alerts
|

Shellfish Toxins − Chemical Studies on Northern Adriatic Mussels

Abstract: During our investigation on toxic mussels from the Northern Adriatic sea, initiated about ten years ago, a number of polyether toxins have been isolated and characterized, some of which represent new additions to the diarrhetic shellfish poisoning (DSP) class of biotoxins and seem to be specific to the Adriatic. In addition, we have also isolated new types of toxins, oxazinins and chlorosulfolipids, whose structures were elucidated by extensive use of 1D and 2D NMR spectroscopic techniques. Some of them could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 77 publications
0
13
0
Order By: Relevance
“…18 Synthetic efforts on marine natural products continue to expand, with reviews covering a variety of topics including trans-fused polycyclic ethers, 19 the convergent syntheses of polycyclic ethers, 20 the use of Suzuki-Miyaura cross-couplings for polycyclic ethers, 21 and the total syntheses of oxazole-containing natural products. 22 Several reviews focus on studies on compounds from specific types of organisms, such as cytotoxic metabolites from marine algae, 23 anticoagulants from marine algae, 24 metabolites of marine-derived fungi, 25 antimicrobials and antifungals from marine microorganisms, 26 toxins from microalgae, 27 enzyme inhibitors from marine microbes, 28 glycosides from sea cucumbers, 29 medicinal and pharmaceutical products from macroalgae, 30 bioactive polypeptides from Anemonia sulcata, 31 metabolites from several species of sponges of the genus Plakortis 32 and specifically from Plakortis simplex, 33 peptide and peptide-like pheromones and kairomones from crustaceans, 34 toxins from Northern Adriatic mussels, 35 metabolites from the gorgonian corals of the genus Junceella, 36 and metabolites from symbiotic bacteria. 37 A broad range of bioactivities of marine natural products is reviewed in several articles, including marine pharmacology in 2000, 38 the merging of the potential of microbial genetics with biological and chemical diversity, 39 drugs and cosmetics from the sea, 40 unconventional natural sources for future drug discovery, 41 new structures and bioactivities for small-molecule natural products, 42 and marine natural products and related compounds in clinical and advanced preclinical trials.…”
Section: Reviewsmentioning
confidence: 99%
“…18 Synthetic efforts on marine natural products continue to expand, with reviews covering a variety of topics including trans-fused polycyclic ethers, 19 the convergent syntheses of polycyclic ethers, 20 the use of Suzuki-Miyaura cross-couplings for polycyclic ethers, 21 and the total syntheses of oxazole-containing natural products. 22 Several reviews focus on studies on compounds from specific types of organisms, such as cytotoxic metabolites from marine algae, 23 anticoagulants from marine algae, 24 metabolites of marine-derived fungi, 25 antimicrobials and antifungals from marine microorganisms, 26 toxins from microalgae, 27 enzyme inhibitors from marine microbes, 28 glycosides from sea cucumbers, 29 medicinal and pharmaceutical products from macroalgae, 30 bioactive polypeptides from Anemonia sulcata, 31 metabolites from several species of sponges of the genus Plakortis 32 and specifically from Plakortis simplex, 33 peptide and peptide-like pheromones and kairomones from crustaceans, 34 toxins from Northern Adriatic mussels, 35 metabolites from the gorgonian corals of the genus Junceella, 36 and metabolites from symbiotic bacteria. 37 A broad range of bioactivities of marine natural products is reviewed in several articles, including marine pharmacology in 2000, 38 the merging of the potential of microbial genetics with biological and chemical diversity, 39 drugs and cosmetics from the sea, 40 unconventional natural sources for future drug discovery, 41 new structures and bioactivities for small-molecule natural products, 42 and marine natural products and related compounds in clinical and advanced preclinical trials.…”
Section: Reviewsmentioning
confidence: 99%
“…Normally, these channels open in response to membrane depolarization and subsequently inactivate, returning to closed configuration during the membrane repolarization. Receptor binding studies with synaptosome preparations from manatee brain showed tritiated PbTx3 binding with an affinity somewhat lower than that of rat and similar to that of fish excitable tissues (Trainer and Baden, 1999;Ciminiello and Fattorusso, 2004). There is also alteration of the normal changes of the voltage-sensitive sodium channels configuration during the depolarization/repolarization processes.…”
Section: Mechanism Of Actionmentioning
confidence: 92%
“…toxicities, as summarized by Plakas and Dickey (2010). Other Karenia species were involved in NSP, whereas some raphidophytes (Chattonella marina, C. antiqua, Fibrocapsa japonica, and Heterostigma akashiwo) were reported to produce brevetoxin-like compounds, but no documented cases of NSP were caused by these species (Landsberg, 2002;Hallegraeff, 2003;Ciminiello and Fattorusso, 2004). Oral toxicity data are not available for any of the brevetoxin shellfish metabolites because isolation of these toxins and their synthesis have been challenging .…”
Section: Brevetoxins Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Three main species of dinoflagellates that produce the toxins are: Alexandrium spp., Gymnodinium and Pyrodinium. 7 Five major classes of shellfish poisoning have been identified: neurotoxic shellfish poisoning (NSP), diarrhetic shellfish poisoning (DSP), paralytic shellfish poisoning (PSP), amnesic shellfish poisoning (ASP) and ciguatera fish poisoning (CSP). Except for ASP all poisoning incidents are caused by biotoxins synthesized by dinoflagellates.…”
mentioning
confidence: 99%